What we learned about headache during the COVID-19 pandemic: literature review - Januškevičiūtė, E.; Grigaitė, J.; Ryliškienė, K. (Neurologijos seminarai, 2023)
Headache is one of the most common neurological symptoms associated with coronavirus disease 19 (COVID-19), which can mimic primary headache phenotypes. COVID-19 and quarantine have affected both the course of primary headache and patient care strategies. The safety of migraine treatment with anti-CGRP (calcitonin gene-related peptides) monoclonal drugs has become important. Another challenge posed by the introduction of mass vaccination is vaccine-related headache, the most common neurological adverse event, and a less common complication, cerebral venous thrombosis. The article provides a brief overview of COVID-19 induced headache and its features, vaccination-induced headache, the impact of COVID-19 and quarantine on primary headache, the safety of anti-CGRP monoclonals, and the advantages and disadvantages of remote consultations on primary headaches.